FREEDOM & IMPARTIAL OF JUDICIARY : ANTARA â€œ PERADILAN BEBASâ€ & â€œPERS YANG BEBAS - Adji, Indriyanto Seno (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
Press of independence adopted by Law No. 40 of 1999 on the Press is an accentuation of the Libertarian Press system which requires the existence of a absolute total